ANALISIS KELAYAKAN INVESTASI PADA PROYEK AIR BERSIH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN MINAHASA SELATAN - Tumbelaka, Hence Rudolf; Supit, Cindy J.; Mandagi, Robert J. M. (JURNAL ILMIAH MEDIA ENGINEERING, 2020)
The supply of clean water is one of the basic human needs and the social-economic rights to be required for the regional and central government to fulfill. In order to facilitate the development of SPAM at South Minahasa Regency, the local government is necessarily expected to have long-term planning to fulfill the demand for clean water. For this is a basic human needs in every activities, therefore an establishment of clean water system that can give optimal benefits and reach the expected planning age are needed, such attempt needs professional management that is sustainable and continually. The purpose of this research is to obtain the potential capacity of clean water supply system in four villages within the capital of Tareran sub-district using PVC typed pipes which before were GIP typed pipes that have exceeded its planning age, resulting change in dimension due to deposition and thickening on wall inside of the pipeand determine economic feasibility from the replacement of Galvanized Iron Pipe (GIP) distribution pipe to Polyvinyl Choloride Pipe (PVC) in 4 (four) villages within the capital of Tareran sub-district.The results obtained from this research and analysis are; (1) 4 inches (100 mm) and 6 inch (150 mm) Polyvinyl Chloride Pipes (PVC) after being technically analyzed are feasible to replace Galvanized Iron Pipes (GIP) that have exceeded planning age with the result for technical analysis of Tareran sub-district’s capital clean water supply production capacity to meet an increase from 230,36 m3/day to 240,84 m3/day. (2) The supply of clean water covers these four villages; RumoongAtas, RumoongAtasDua, LansotTimurdanLansot, which economically speaking for the capital of Tareran sub-district are feasible to invest after being examined with several investment measures which are Net Present Value (NPV) for Rp8.810.252.490 (NPV > 0), Break Even Point (BEP) with investment value return to occur in 2nd year of the 1st month (2 years 1 month) exactly in 2019 or under the operational planning age and assuming 12% level of interests still produces positive valuewhere IRR value > 12% or still above the level of expected minimum interests of 10%, Keywords: Clean Water, Feasibility, Galvanized Iron Pipe, PolynivylCholoride Pipe, Based on Net Present Value, Break-even Point, Internal Rate of Return